2012
DOI: 10.1094/mpmi-08-11-0204
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characteristics of an Endophyte Community Colonizing Rice Roots as Revealed by Metagenomic Analysis

Abstract: Roots are the primary site of interaction between plants and microorganisms. To meet food demands in changing climates, improved yields and stress resistance are increasingly important, stimulating efforts to identify factors that affect plant productivity. The role of bacterial endophytes that reside inside plants remains largely unexplored, because analysis of their specific functions is impeded by difficulties in cultivating most prokaryotes. Here, we present the first metagenomic approach to analyze an end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
398
0
23

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(440 citation statements)
references
References 49 publications
19
398
0
23
Order By: Relevance
“…Due to potential hydroxyl radical formation following reduction of molecular oxygen in the presence of ferrous iron catalysts, drimane sesquiterpenes may cause oxidative stress in the affected plant tissue. A study exploring the metagenome of the rice root endophytic community identified the expression of glutathione synthase genes, a metabolite that is known to mitigate oxidative stress, as consequence of endophyte colonization amongst others (Sessitsch et al, 2012). Tolerance against oxidative stress may represent a widespread trait in soil microbes; their nutrition depends on the decomposition of organic polymers, an oxidative process that also may involve the formation of hydroxyl radicals in the Fenton reaction or the activity of oxidative enzymes (ten Have and Teunissen, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Due to potential hydroxyl radical formation following reduction of molecular oxygen in the presence of ferrous iron catalysts, drimane sesquiterpenes may cause oxidative stress in the affected plant tissue. A study exploring the metagenome of the rice root endophytic community identified the expression of glutathione synthase genes, a metabolite that is known to mitigate oxidative stress, as consequence of endophyte colonization amongst others (Sessitsch et al, 2012). Tolerance against oxidative stress may represent a widespread trait in soil microbes; their nutrition depends on the decomposition of organic polymers, an oxidative process that also may involve the formation of hydroxyl radicals in the Fenton reaction or the activity of oxidative enzymes (ten Have and Teunissen, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Complementary to such cultivation approaches, the direct sequencing of complex mixtures of DNA from various organisms of a habitat (metagenomics) reveals the metabolic capacity of a microbiome. In rice, numerous microbial traits such as nitrogen fixation, the flagellum, protein secretion systems, or quorum sensing, and their habitat specificity were predicted using metagenomics (17,18).…”
Section: Toolsmentioning
confidence: 99%
“…Flooding impedes the transport of oxygen, so that the bulk of the soil becomes anoxic and supportive for anaerobic degradation of organic matter and CH 4 production (Liesack et al 2000). However, the rice gas vascular system allows the transport of oxygen into the roots and the rhizosphere thus providing a habitat for both aerobic and anaerobic bacteria involved in redox reactions of the C, N and S cycle (Liesack et al 2000;Sessitsch et al 2012). Maize, on the other hand, is a crop grown in aerated upland soil, which is usually oxic and supportive for aerobic degradation of organic matter to CO 2 .…”
Section: Introductionmentioning
confidence: 99%